Experimental study on the hydrogen diffusion across an individual grain boundary in pure nickel by scanning Kelvin probe force microscopy - Ma, Zhaoxiang; Wu, Weiyi; Liu, Zhongli; Cheng, Kaiyu; Wang, Chengxu; Zhu, Kunjun (Scripta materialia, 2024)
There are few existing experimental studies on the controversial diffusion behavior of hydrogen atoms across an individual grain boundary (GB). In this study, by combining Electron Back Scattered Diffraction (EBSD) and scanning Kelvin probe force microscopy (SKPFM) techniques, the transverse diffusion behavior of hydrogen atoms across a random GB with a misorientation of 45° within the directionally solidified high purity nickel was directly observed. The results suggest that the hydrogen atoms diffused perpendicular to the studied GB will be trapped by this GB, resulting in hydrogen segregation at the GB. In addition, the studied GB acts as a two-dimensional barrier that can block the transverse diffusion of hydrogen atoms. This present study reveals the real role played by a specific random GB on the hydrogen transverse diffusion and enriches the existing experimental research for intergranular diffusion. [Display omitted]